Comparative Analysis of Algorithm of Naive Bayes and C4.5 On Employee Performance Classification - Sadikin, Muhammad; Batubara, Rini Oktari (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 13 No 2 (2024): JELIKU Volume 13 No 2, November 2024, 2024)
Employee performance appraisal is one of the supporting factors to increase the productivity of an agency's performance. Performance appraisal is needed to determine the level of success of each employee's performance and is used to assess success in accordance with the objectives set in order to realize the mission and vision of a company. The employee performance appraisal system that runs at the Main Potential University is outlined in the Standard Operating Procedure (SOP) document. There are 10 criteria that serve as benchmarks for assessment, namely work discipline, administrative discipline, reliability, maturity and personal integrity, morale, communication and cooperation, adherence to work principles, quantity of work results, quality of work results, and concern for the organization. The purpose of this study was to determine the level of accuracy of the two methods used by using Weka 3.8 tools using performance evaluation data mining Cross Validation 2,5,6 and 10 Fold Validation as a comparison